Fun Problems in Geometry and Beyond - Khesin, B.; Tabachnikov, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2019)
We discuss fun problems, vaguely related to notions and theorems of a course in differential geometry. This paper can be regarded as a weekend "treasure chest" supplementing the course weekday lecture notes. The problems and solutions are not original, while their relation to the course might be.